Virtual power plant: managing synergies and conflicts between transmission system operator and distribution system operator control objectives - Pudjianto,D; Strbac,G; Boyer,D (IET, 2017)
In this study, the implementation of virtual power plant (VPP) as a means to coordinate the use of distributed resources for different control objectives by transmission system operator and distribution system operator is described. In order to illustrate the concept, a range of illustrative studies demonstrating the application of VPP concept on a real 11 kV system in Brixton will be presented, using data from the Low Carbon London project. The studies demonstrate the changes in the operating characteristics of the VPP area over a range of system operating conditions.